Workshop Penulisan Karya Tulis Guru SMA Unggul Cut Nyak Dhien Kota Langsa - Iden Rainal Ihsan; Roni Priyanda; Sri Jayanthi (LPPM UNINUS, 2022)
Community service in the form of workshop activities is intended to increase the insight and experience of 26 educators at Cut Nyak Dhien High School Langsa City in writing and publishing scientific papers. The writings made are directed in the form of the results of design-based research (DBR) activities, namely in the form of learning designs made by educators that are tailored to the needs and problems contained in each class. This series of community service activities consists of 3 groups of activities. The first group of activities is the stage of preparation and data mining by conducting interviews and observations. Second, core activities were carried out, namely practical workshops and writing of DBR results. The workshop activity was closed with mentoring activities for writing scientific papers. Judging from the survey responses of participants, this workshop activity received a positive response in terms of implementation, presenters, and the usefulness of the material.